Book Reviews (Historia, 2021)
1. Burckhardt, C. J.: Richelieu and his age2. Ulmann, E.: Designs on Life3. Shaw, A. G. L. (ed.): Great Britain and the Colonies. Series: Debates in Economic History 4. Minchinton, W. E. (ed.): The growth of English overseas trade in the 17th century, with a bibliographical essay. Series: Dabates in Economic History 5. Creig, D. E.: Herbert Baker in South Africa